Improving the Credibility of Child Sexual Assault Victims in Court: The Impact of a Sexual Assault Nurse Examiner. (August 2015) - Golding, Jonathan M.; Wasarhaley, Nesa E.; Lynch, Kellie R.; Lippert, Anne; Magyarics, Casey L.
<x xml:space="preserve">Abstract</x> The present study investigated the influence of a sexual assault nurse examiner's (SANE's) testimony on mock juror perceptions of a child or adolescent victim of child sexual assault. Community members (N = 252, 156 females) read a fictional criminal trial summary of a child sexual assault case in which the victim was 6 or 15 years old and the prosecution presented medical testimony from a SANE or a traditional registered nurse (RN), or did not present medical testimony. Mock jurors were more likely to render guilty verdicts when a SANE testified compared with the other two testimony conditions. In addition, pro‐victim judgments (e.g., sympathy toward the victim) and negative defendant judgments (e.g., anger toward the defendant) mediated this relation. Finally, cognitive network representations of the case demonstrated that the RN and no‐medical‐testimony groups were similar and the SANE group was distinct from the other two conditions. We discuss these results in terms of the implications of SANE testimony in child sexual assault court cases. Copyright © 2015 John Wiley & Sons, Ltd.